JUDUL PENELITIAN :â€BALI NDESO MBANGUN DESOâ€ DAN KETAHANAN PANGAN DAERAH PROVINSI JAWA TENGAH. - WINDIANI, RENI (Politika: Jurnal Ilmu Politik, 2012)
AbstractNowadays food can be categorized as one of the most important aspect of human right.Regarding to that condition, state should provide food accessibility and availability for the society. Dueto big number of its population, Indonesia faces complex problem in order to fulfill of food need of itspeople. In this respect food security policy becoming focuses of Indonesian development policyespecially its agriculture development policy. One of the most considerable provinces in Indonesiannational agriculture is Central Java, by reason of its 17% contribution on national rice production.Further, in contrast to national food condition that experienced rice import dependency, Central Javaâ€Ÿsfood security currently experiencing steady condition. This condition raised up interesting researchquestion: is there any correlation between central javaâ€Ÿs steady food condition and Central JavaGovernor Candidate Bibit-Rusriâ€žs Campaign slogan â€œBali Ndeso Mbangun Desoâ€ in the Central JavaGovernor Election on 2008. Using qualitative method and type of descriptive research, this inquiryshowed that the moral movement â€œBali Ndeso Mbangun Desoâ€ has contributed positively on foodsecurity in Central Java.Key words : food security, bali ndeso mbangun deso, rice production.